Winter Night-Warming Improves Post-anthesis Physiological Activities and Sink Strength in Relation to Grain Filling in Winter Wheat (Triticum aestivum L.) - Fan, Yonghui; Tian, Zhongwei; Yan, Yanyan; Hu, Chenxi; Abid, Muhammad; Jiang, Dong; Ma, Chuanxi; Huang, Zhenglai; Dai, Tingbo (Frontiers in Plant Science, 2017)
The diurnal and seasonal temperature rising patterns “asymmetric warming”, plays an important role in crop distribution and productivity. Asymmetric warming during the early growth periods of winter wheat (Triticum aestivum L.) profoundly affects vegetative growth and post-anthesis grain productivity, but the underlying physiological mechanism is still unclear. We conducted field experiments from 2012 to 2014 using two wheat cultivars, namely, Yangmai-13 (vernal type) and Yannong-19 (semi-winter type), to investigate the influences of night-warming during the winter (warming by 1.56−1.67°C from tillering to jointing) or during the spring (warming by 1.78−1.92°C from jointing to booting) on post-anthesis physiological activities and grain-filling processes. Both night-warming treatments enhanced the source activity by increasing flag leaf area, chlorophyll content, and photosynthetic capability in both cultivars compared with those of the control. The night-warming treatments caused an increase in the antioxidant activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in the flag leaves of both cultivars, while ROS contents such as superoxide anion radical (O2•−) and hydrogen peroxide (H2O2) decreased. Moreover, the expression levels of Rubisco activase B (RcaB), major chlorophyll a/b-binding protein (Cab), chloroplast Cu/Zn superoxide dismutase (Cu/Zn-SOD), mitochondrial manganese superoxide dismutase (Mn-SOD), and catalase (CAT) genes were upregulated at anthesis and were associated with higher photosynthetic capacity and antioxidant activities. Furthermore, night-warming improved sink activities by increasing the concentrations of grain indole-3-acetic acid (IAA) and cytokinins (CTK) as well as the sucrose synthase (SS) activity for both cultivars. Winter night-warming showed greater potential for improving source strength and grain filling, with consistent performance in both cultivars compared with that of spring night-warming. We concluded form these results that night-warming can improve source and sink capacities in winter wheat, and winter night-warming has greater advantages in this respect than does spring warming.